2009
DOI: 10.1002/dvdy.22116
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell maturation in the developing vertebrate retina

Abstract: Progenitor cells in the developing retina initially divide so that each division produces two cells that divide again. Subsequently, progenitor cells change their mode of division so that one or both cells produced by a division can withdraw from the mitotic cycle and differentiate. We asked how these two progenitor cell stages differ molecularly and what controls the switch in the mode of division. We show that early preneurogenic progenitor cells express the transcription factor, Sox2, and the Notch ligand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Further supporting this identity, cells in both the apical plate and lateral ectoderm that express SoxC also express Delta (Fig. 1D,E), which is characteristic of neural precursors in embryos (Vässin et al, 1987;Yang et al, 2009). Furthermore, when DeltaNotch signaling is blocked by treatment with DAPT, which is a gamma secretase inhibitor of Notch signaling, SoxC-expressing cells increase in number and form small clusters (Fig.…”
Section: Soxc Function Is Required Downstream Of Six3 For Developmentmentioning
confidence: 60%
“…Further supporting this identity, cells in both the apical plate and lateral ectoderm that express SoxC also express Delta (Fig. 1D,E), which is characteristic of neural precursors in embryos (Vässin et al, 1987;Yang et al, 2009). Furthermore, when DeltaNotch signaling is blocked by treatment with DAPT, which is a gamma secretase inhibitor of Notch signaling, SoxC-expressing cells increase in number and form small clusters (Fig.…”
Section: Soxc Function Is Required Downstream Of Six3 For Developmentmentioning
confidence: 60%
“…bHLH transcription factors have been shown to be integral during embryonic development, playing roles in myogenesis, heart development, hematopoiesis, and neurogenesis (34). Of the various bHLH transcription factors predicted to bind the Ebox, E2A and NeuroD1 are expressed in developing vertebrate retina (41), and have been reported to play a role in retinal neurogenesis and differentiation (42,43). In these instances, E2A and NeuroD1 are considered to be proneural bHLH proteins, acting as transcriptional activators.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown generalized Dll1 expression before retinal neuron differentiation (Haddon et al, 1998;Kay et al, 2005;Nelson and Reh, 2008;Rocha et al, 2009;Yang et al, 2009). We decided to investigate this issue by performing a systematic spatiotemporal analysis in the chick retina to evaluate the expression pattern of Dll1 and other genes involved in the neurogenic process.…”
Section: Dll1 Is Expressed Before the Initiation Of Neurogenesis In Tmentioning
confidence: 98%
“…For instance, in the early zebrafish embryo, strong deltaD expression delineates the whole developing retina a few hours before the initiation of neurogenesis in this tissue (Haddon et al, 1998;Kay et al, 2005). In both the avian and murine retina, Delta-like 1 (Dll1) is expressed more peripherally than its homolog Dll4, being detected in a high proportion of mitotically active progenitor cells (Nelson and Reh, 2008;Rocha et al, 2009;Yang et al, 2009). In Drosophila, Delta (Dl) expression has been shown to precede achaete protein accumulation in microchaeta proneural stripes (Parks et al, 1997).…”
Section: Introductionmentioning
confidence: 99%